Plasticidade, causação mental e semiose: Peirce e a neurociência do século XXI - Costa, Monica Aiub da (2015)
This work is dedicated to review the concept of semiosis in clinic, starting from the articulation of the concepts of plasticity, mental causation and semiosis in Charles Sanders Peirce's philosophy, and in neuroscience. Its development perceived the means of semiosis and its implications in therapy, especially in the mental causation issues, considering that physical states and mental states interact from semiotic processes, generating plasticity, both in cellular and cognitive levels. Were addressed, specially, the concepts of plasticity, mental causation and semiosis, articulated from Peirce's phenomenology, metaphysics and cosmology. The dialogue stablished between Peirce and neuroscience provided the magnification of the semiosis concept in clinical listening and its consequent implications in making diagnoses, since, starting from Peirce's contributions, semiosis can't be understood in a typological way, due to the fact of being an open system, an auto generated and creative network of signs, covering aspects from cells to incorporated technology, and constituting in a plastic way, continuous, in multiple interactions with innovations promoted by chance